Calculation of optical functions of exciton and electron transitions by means of kramers-kronig relations in CuAlS2 crystals - Stamov, Ivan (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2013)
Excitonic reflection spectra of CuAlS2 crystals were measured at a temperature of 10 K for E||c and Ec polarizations. The shapes of the lines of ground states of Г4 and Г5 excitons were calculated by means of the Kramers-Kronig relations. Exciton parameters and the values of energetic gaps (Г7Г6, Г6Г6, and Г7Г6) were determined. Optical reflection spectra in the depth of absorption band (Еg - 6 eV) were measured at 80 K for E||c and Ec polarizations. Optical functions n, k, ε1, ε2, d2ε1/dE2 and d2ε2/dE2 were calculated for both polarizations. The revealed peculiarities are ascribed to electronic transitions in the frame of theoretical calculations of the band structure for crystals from this group.